The use of angiotensin receptor blockers is associated with greater recovery of cardiac function than angiotensin-converting-enzyme inhibitors among patients with dilated cardiomyopathy. (14th October 2021) - Enzan, N; Matsushima, S; Ide, T; Tohyama, T; Funakoshi, K; Higo, T; Tsutsui, H
Abstract: Background: We previously showed that angiotensin-converting-enzyme inhibitors (ACEi) or angiotensin receptor blockers (ARB) were associated with heart failure with recovered ejection fraction (HFrecEF) in patients with dilated cardiomyopathy (DCM). However, the different effects of these drugs on cardiac reverse remodeling have not been fully elucidated. The aim of this study was to assess comparative effectiveness of ACEi versus ARB on recovery of left ventricular ejection fraction (LVEF) among patients with DCM. Methods: We analyzed the clinical personal records of DCM, a national database of Japanese Ministry of Health, Labour and Welfare, from 2003 to 2014. Patients with LVEF <40% and on either ACEi or ARB were included. Eligible patients were divided into two groups according to the use of ACEi or ARB. A one-to-one propensity case-matched analysis was used. A propensity score was estimated by fitting a logistic-regression model which adjusted for age, sex, duration of HF, NYHA functional class (I-II vs. III-IV), systolic blood pressure, diastolic blood pressure, heart rate, atrial fibrillation, pacing, left bundle branch block, LVEF, hypertension, diabetes mellitus, hyperuricemia, chronic kidney disease, B-type natriuretic peptide (BNP), beta-blockers, mineralocorticoid receptor antagonists, loop diuretics, thiazides, digitalis, amiodarone, and oral inotropes. The primary outcome was defined as LVEF ≥40% at 3 years of follow-up. Results: Out of 4, 618 eligible patients, 2, 238 patients received ACEi and 2, 380 patients received ARB. Propensity score matching yielded 1, 341 pairs. Mean age was 56.0 years and 2, 041 (76.1%) was male. Mean LVEF was 27.6%, and median duration of HF was 1 year. The primary outcome was observed more frequently in ARB group than in ACEi group (59.8% vs. 54.1%; odds ratio [OR] 1.26; 95% confidence interval [CI] 1.08–1.47; P=0.003). The change in LVEF from baseline to 3 years of follow-up was greater in ARB group than in ACEi group (15.8±0.4 vs. 14.0±0.4%, P=0.002). In the ACEi group, 946 patients (70.6%) continued to receive ACEi at 3 years of follow-up, while 1, 088 patients (81.3%) continued to receive ARB in the ARB group. Per-protocol analysis consistently showed that ARB increased the prevalence of HFrecEF (62.0% vs. 54.0%; OR 1.39; 95% CI 1.17–1.66; P<0.001). Subgroup analysis showed that ARB increased frequency of HFrecEF regardless systolic blood pressure, heart rate, LVEF, chronic kidney disease, and concomitant use of beta-blockers and mineralocorticoid receptor antagonists. Conclusions: The use of ARB was associated with HFrecEF more frequently than ACEi among patients with DCM and reduced LVEF. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Health Sciences Research Grants from the Japanese Ministry of Health, Labour and Welfare (Comprehensive Research on Cardiovascular Diseases)Japan Agency for Medical Research and Development (AMED) grant